Conjugados fluorescentes produzidos com IgY de galinhas hiperimunizadas - Simone Machado Mendes de Sousa (2008)
Two groups of hens were immunized with canine IgG and rabies virus suspension to produce fluorescent conjugates using IgY extracted from egg yolks. The egg yolks were collected during the immunizationprocess and the aqueous phase was separated from the lipidic phase through delipidation. IgY anti-dog and anti-rabies were measured weekly with ELISA to generate an antibody production curve. After purification through ammonium sulfate precipitation, the IgY were conjugated with fluorescein isothiocyanate. The produced conjugates were titrated on reagent sera positive for visceral leishmaniasis and on brain tissues positive for rabies in indirect and direct immunofluorescence reaction, respectively. After the determination of the dilution study, the combined were assessed for revelation in 60 dog sera positive and non-reactive for visceral leishmaniasis by RIFI and in 60 bovine brain prints positive andnon-reactive for rabies with RIFD. The conjugates showed excellent results with relative sensitivity and specificity of 96.66% and 93.33% with RIFI, and 100% with RIFD, thus demonstrating the possibility of its use in leishmaniasis and rabies routine diagnosis. These results show that hens can replace mammals in polyclonal antibody production, thereby decreasing the need of blood collection and euthanasia of mammals and prioritizing the use of a noninvasive method of immunoglobulin extraction from eggs.